2008
DOI: 10.1080/14992020701870197
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation in deaf children with associated disabilities: Challenges and outcomes

Abstract: The issue of cochlear implantation in deaf children with associated disabilities is an emerging subject. Currently, there is no consensus on whether to implant children with multiple impairments; moreover, it may be difficult to evaluate these children with standard tests pre- or post-implantation. In addition, these children often have poor speech perception and language skills, making assessment more difficult. Despite these factors, these children often receive important benefits in daily life, with an over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
101
2
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 23 publications
4
101
2
9
Order By: Relevance
“…However, considering that it has a very high population of 765 children, we can assume that the population includes children with varying degrees of hearing loss, age at onset of deafness, development of motor skills and memory, family size and background. Furthermore, according to Berrettini et al [32] and Fortnum et al [33] , approximately 30-40% of hearing-impaired children also have additional disabilities, making it thus very like-ly that our study population included children with additional needs. Hence we may say that our standardised values are likely to reflect additional factors influencing speech perception outcomes to a certain degree and that these values can be considered to be heterogeneous and generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering that it has a very high population of 765 children, we can assume that the population includes children with varying degrees of hearing loss, age at onset of deafness, development of motor skills and memory, family size and background. Furthermore, according to Berrettini et al [32] and Fortnum et al [33] , approximately 30-40% of hearing-impaired children also have additional disabilities, making it thus very like-ly that our study population included children with additional needs. Hence we may say that our standardised values are likely to reflect additional factors influencing speech perception outcomes to a certain degree and that these values can be considered to be heterogeneous and generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…Intellectual disability and additional handicaps made it difficult to develop receptive and expressive language skills after implantation [6] , besides impairments across the areas of language, speech, and oro-motor functions in patients with KS [7] . Regardless of whether a child has a hearing loss only or has a disability in addition, there is a relationship between increased age at implantation and poor performance [8] .…”
Section: Discussionmentioning
confidence: 99%
“…the issue of candidacy to cochlear implantation is more complex [4][5][6][7]. Several authors have reported that deaf children with additional disabilities achieve lower perception scores and language development than children without additional disabilities [5][6][7][8][9]. However, the majority of authors agree to the fact that cochlear implantation in deaf children with additional disabilities leads at least to an increased connectivity and interest in the environment and social interactions that contribute to significantly improve their quality of life [5][6][7]10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Usher syndrome, Waardenburg syndrome, CHARGE syndrome, etc.) the issue of candidacy to cochlear implantation is more complex [4][5][6][7]. Several authors have reported that deaf children with additional disabilities achieve lower perception scores and language development than children without additional disabilities [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%